1970
DOI: 10.1590/s0004-282x1970000400010
|View full text |Cite
|
Sign up to set email alerts
|

Forma miopática da cisticercose

Abstract: A ocorrência de manifestações clínicas durante a evolução de cisticercose muscular tem sido verificada em reduzido número de pacientes. Tivemosa oportunidade de estudar um caso com infestação muscular maciça que julgamos de interesse relatar. Hemossedimentação:54 mm na primeira hora. Na urina: sedimento, 10 a 15 leucó-citos com raros agrupamentos e 1 e 2 hemácias por campo; pesquisas de substân-cias proteicas e redutores negativas. No sangue: uréia 12,8 mg/100 ml; creatinina 1,0 mg/100 ml; glicose 80 mg/100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Jolly & Pallis (1971) reviewed seven such previously reported cases and presented two more all from India. since then, two other patients from this country (Rao et al, 1972;Sawhney et al, 1976) and one from Brazil (Armburst-Figueiredo et al, 1970) have been reported. The scanty literature on muscle cysticercosis provides limited information and the pathogenesis of the condition is rather uncertain.…”
Section: Discussionmentioning
confidence: 93%
“…Jolly & Pallis (1971) reviewed seven such previously reported cases and presented two more all from India. since then, two other patients from this country (Rao et al, 1972;Sawhney et al, 1976) and one from Brazil (Armburst-Figueiredo et al, 1970) have been reported. The scanty literature on muscle cysticercosis provides limited information and the pathogenesis of the condition is rather uncertain.…”
Section: Discussionmentioning
confidence: 93%
“…[5][6][7][8] The muscle biopsy is usually normal, with no pathologic evidence of denervation, dystrophic change, or hypertrophy, 7 but Sawhney and others 5 reported active myositis with changes in muscle fibers apart from an inflammatory reaction around cysts in a patient with pseudohypertrophic myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…[254,[291][292][293][294][295][296] The clinical features depend on the location of the cyst, the cyst burden, and the host reaction but most of patients' present painless, rubbery nodules around 2 cm in diameter, which do not carry any risk to the patient's health or can present pseudotumor, mass, pseudohypertrophy [295][296][297][298] and myalgias. [298] A positive diagnosis is established solely by incision and examination of the interior, where the parasite will be found.…”
Section: Limbs Cysticercosismentioning
confidence: 99%
“…Clinical manifestations include vague abdominal discomfort, tender or painless nodules. This presentation is more commonly seen in patients presenting disseminated cysticercosis [283,292,293,[296][297][298][300][301][302][303] rather than isolated cysticercosis. [277-282, 286-289, 294] …”
Section: Extra-abdominal Cysticercosismentioning
confidence: 99%